Yves Béhar : fuseproject - Benezra, Neal; Keffer, Ruth; Rosa, Joseph; Exhibition. Yves Béhar : fuseproject. SFMOMA (San Francisco Museum of Modern Art) San Francisco. 2004-03-26. 2004-10-03 (San Francisco : SFMOMA (San Francisco Museum of Modern Art) San Francisco, 2004)
Yves Béhar's innovative, narrative-based approach situates him at the forefront of industrial design. In collaboration with forward-thinking companies such as MINI, Birkenstock, and HP, he creates objects and product concepts aimed at today's tech-savvy, visually literate, environmentally conscious consumer. The first American publication devoted to the work of Béhar and the design firm, fuseproject, this catalogue - which accompanies an exhibtion at the San Francisco Museum of Modern Art - is the second volume in the Museum's Design Series. An essay by Joseph Rosa, SFMOMA's Helen Hilton Raiser Curator of Architecture and Design, examines Béhar's affinities for brand fusion, high-tech materials, and, above all, objects that are satisfying to hold and use. Texts by curatorial associate Ruth Keffer explore the designer's most important recent projects, including a novel line of products for the revamped MINI, distinctive bottles and packaging for parfume and cosmetics companies, a Teflon-coated cashmere windbreaker, and a modular, customizable structure known as the Trium Erector.
project information, selected bibliography p. 46-47, 48
Engels
boek
Keywords: Béhar, Yves